Efeito agudo da vibração mecânica na direção da resultante das forças de contração voluntária máxima no desempenho de Sprints em atletas de Montain Bike - Pedro Augusto Santos Almeida (2018)
Introduction: In sports, several mechanisms have been studied in recent years aiming to achieve superior physical performances. One of these mechanisms is post-activation potentiation (PAP), which consists of obtaining increased muscle performance through a previous conditioning activity. Maximum voluntary contraction (MVC) and mechanical vibration (MV) have been presented as conditioning activities capable of provoking PPA and could be a method to achieve superior performances in short duration explosive activities. Objective: To verify the acute effect of MVC with or without addition of mechanical vibration in anaerobic performance in 15-s sprint. Methods: We evaluated 10 well-trained Mountain Bike athletes who underwent 10s of MVC and MVC+MV with subsequent 15-s sprint with individualized resistance load for the highest power application, in three situations of different intervals, 1, 6 and 11 minutes after the conditioning activity, besides the control situation that was constituted of the sprint in the three intervals with previous traditional heating without application of MVC+MV and MVC. Results: No significant differences were found in the values of peak power, mean power and time to peak power between the experimental situations in any of the tested intervals. Conclusion: Both the MVC protocol and the MVC+MV protocol were not sufficient to increase the anaerobic performance of well-trained Mountain Bike athletes in 15-s sprints, however, the individualization of the optimal resistance load was shown to be of paramount importance for the identification of maximum values in anaerobic tests.